2019
DOI: 10.3390/cancers11040571
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Multi-Kinase Inhibitors Causes Differential Toxicities on Skeletal and Cardiac Muscles

Abstract: Despite recent progress, chemotherapy remains the preferred treatment for cancer. We have shown a link between anticancer drugs and the development of cachexia, i.e., body wasting accompanied by muscle loss. The multi-kinase inhibitors (MKIs) regorafenib and sorafenib, used as second-line treatment for solid tumors, are frequently accompanied by several side effects, including loss of muscle mass and strength. In the present study we aimed to investigate the molecular mechanisms associated with the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
1
26
1
Order By: Relevance
“…An additional consideration is how chemotherapy may impact the cachectic phenotype in this model of LM. We and others have previously indicated that chemotherapy alone can induce muscle wasting and weakness (Barreto et al, 2017(Barreto et al, , 2016aHuot et al, 2019;Hain et al, 2019a,b). As formation of LM exacerbated muscle wasting in the present study, it will be important to examine whether addition of anticancer treatments may further aggravate the loss of muscle mass.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An additional consideration is how chemotherapy may impact the cachectic phenotype in this model of LM. We and others have previously indicated that chemotherapy alone can induce muscle wasting and weakness (Barreto et al, 2017(Barreto et al, , 2016aHuot et al, 2019;Hain et al, 2019a,b). As formation of LM exacerbated muscle wasting in the present study, it will be important to examine whether addition of anticancer treatments may further aggravate the loss of muscle mass.…”
Section: Discussionmentioning
confidence: 85%
“…To assess skeletal muscle atrophy, 10-μm-thick cryosections of tibialis anterior muscles taken at the mid-belly were processed for immunostaining as described previously (Huot et al, 2019). Briefly, sections were blocked for 1 h at room temperature and incubated overnight at 4°C with a dystrophin primary antibody [1:50, #MANDRA1(7A10), Developmental Studies Hybridoma Bank], followed by a 1 h secondary antibody (AlexaFluor 594, 1:1000, A21125, Thermo Fisher Scientific) incubation at room temperature.…”
Section: Muscle Csamentioning
confidence: 99%
“…Though the goal of the study to examine cachexia in a context of CRC LM was achieved, future studies may consider using lower doses of C26 tumor cells or perhaps other CRC cells that may allow the progression of cachexia to extend beyond 2 weeks. Moreover, in the present study, we did not take into consideration whether the administration of chemotherapeutics further aggravate muscle wasting, especially considering that our lab and others have demonstrated that several anticancer compounds induce cachexia independently of their effects on tumor growth (24,26,27,29,30,60). Lastly, another limitation of the current study was the focus on male animals, leaving out possible sex differences in response to LMs.…”
Section: Discussionmentioning
confidence: 92%
“…Muscle CSA. To assess skeletal muscle atrophy, 10 μm-thick cryosections of tibialis anterior muscles, taken at the midbelly, were processed for immunostaining as described previously (30). Briefly, sections were blocked for 1 hour at room temperature and incubated overnight at 4˚C with a dystrophin primary antibody (Developmental Studies Hybridoma Bank, Iowa City, Iowa, USA; MANDRA1[7A10]), followed by a 1-hour secondary antibody (AlexaFluor 594, A-11032, Thermo Fisher Scientific) incubation at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In an animal study, regorafenib has been shown to cause skeletal muscle loss through a possible mechanism including increasing levels of autophagy-dependent protein markers and abnormal mitochondrial homeostasis via ERK1/2 and glycogen synthase kinase 3 beta (GSK3β) pathways [ 46 ]. In humans, one study [ 29 ], evaluating 22 CRC patients treated with regorafenib, found a statistically significant skeletal muscle loss during treatment (median SMI change: −2.75 cm 2 /m 2 ; p < 0.0001).…”
Section: Impact Of Tki Treatment On Muscle Wastingmentioning
confidence: 99%